Effectiveness of Online Learning During the Covid-19 Pandemic at SMK Negeri 1 Bulukumba - Jamaluddin, Jamaluddin; Nurhaliza, Nurhaliza; Nasrullah, Muh.; Supriadi, Supriadi (Pinisi Journal of Education and Management, 2022)
Effectiveness is the success that results from an effort made to achieve goals according to the time period and the expected results are also appropriate. The purpose of this study was to determine the effectiveness of online learning, to determine the supporting and inhibiting factors of online learning during the Covid-19 pandemic at SMK Negeri 1 Bulukumba. To find out the purpose of this research, a qualitative descriptive research was used. There were 5 informants in this study using data collection techniques through observation, interviews, and documentation. The data obtained from the research results were then processed using data analysis techniques consisting of data collection, data condensation, data presentation and drawing conclusions.